Community Based Forest Management License: The Urgency of Forest Management for Human Development in Indigenous Peoples - Hafsah Aryandini; Abel Parvez (Veteran Law Review, 2023)
The position of customary law communities ' property rights (MHA) over customary forests has not been fully protected by law which causes conflicts regarding customary forests. Weak legal protection leads to discrimination for MHA, namely by loss of residence, loss of agricultural land, and even leading to punishment for defending its rights. In fact, the existence of Indigenous Peoples has been guaranteed in the constitution, namely in Article 18B of the 1945 NRI Constitution. However, in reality, the problem of property rights to customary forests is still often encountered and even boils down to human rights violations, namely the criminalization of Indigenous Peoples who are fighting for their rights. The postulate gives rise to two formulations of the problem. First, what are the problems with forest management regulation on the protection and empowerment of Indigenous Peoples? Second, How is the concept of forest management that protects and empowers Indigenous Peoples in accordance with the ius constituendum? To answer this problem, the author recommends improvements related to existing arrangements and the establishment of government policies as a concrete effort in enforcing the rights of MHA.  Existing laws must provide protection and protection of the human rights of indigenous peoples and be accompanied by customary forest management based on the Community Based Forest Management (CBFM) License as a mechanism in settlement and to protect and implement MHA.